2017
DOI: 10.4103/2229-5151.201962
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine overdose presenting with acute muscle toxicity

Abstract: Olanzapine is an atypical antipsychotic drug that is being increasingly used as an intentional overdose. It usually presents with reduced and fluctuating level of consciousness and coma. It may rarely present with muscle toxicity by binding to HT2A receptor in skeletal muscle and increasing its permeability. We report a case of such poisoning which had no obvious symptoms but was brought to emergency due to overdose and was found to have acute muscle toxicity as evidenced by raised creatine phosphokinase (CPK)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Interestingly, the muscle transcript data from this study further suggested a transition from slow muscle fibers to fast-glycolytic fibers that are more susceptible to atrophy. Accordingly, acute muscle toxicity has been reported following high-dose OLZ administration in humans (Keyal et al, 2017; Waring et al, 2006). These data highlight excessive adipose accretion and muscle impairment as important metabolic abnormalities associated with OLZ use, even in the absence of weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the muscle transcript data from this study further suggested a transition from slow muscle fibers to fast-glycolytic fibers that are more susceptible to atrophy. Accordingly, acute muscle toxicity has been reported following high-dose OLZ administration in humans (Keyal et al, 2017; Waring et al, 2006). These data highlight excessive adipose accretion and muscle impairment as important metabolic abnormalities associated with OLZ use, even in the absence of weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle (*) -Olanzapine Brain stem (Anwar et al, 2016) Acute muscle toxicity (Keyal et al, 2017) Pancreatitis (Kerr et al, 2007) Repatha (Evolocumab) -Muscle-related statin Intolerance (Nissen et al, 2016) -Risedronate (actonel) Ocular myasthenia (Raja et al, 2007) Muscle weakness (Badayan and Cudkowicz, 2009) Gastrointestinal cancer (Vinogradova et al, 2013) Sofosbuvir Ocular surface (Salman, 2016) Myositis (Patel et al, 2015) Pancreatitis (Margapuri and Jubbal, 2019) Teriparatide -Muscle cramp (Kakaria et al, 2005) Pancreatitis (*) *Reported side effects.…”
Section: Cisplatinmentioning
confidence: 99%
“…Olanzapine is an antipsychotic drug, classified within the atypical antipsychotics. The psychiatrists use olanzapine to manage schizophrenia (especially the negative symptoms) ( 9 ) and bipolar disorder ( 10 ). Side effects include extrapyramidal and anticholinergic symptoms ( 9 , 11 ), weight gain, hypertriglyceridemia, hypercholesterolemia, hyperglycemia in patients with diabetes mellitus, galactorrhea, amenorrhea, gynecomastia, erectile dysfunction, neutropenia, seizure threshold lowering, personality changes and suicidality ( 10 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The psychiatrists use olanzapine to manage schizophrenia (especially the negative symptoms) ( 9 ) and bipolar disorder ( 10 ). Side effects include extrapyramidal and anticholinergic symptoms ( 9 , 11 ), weight gain, hypertriglyceridemia, hypercholesterolemia, hyperglycemia in patients with diabetes mellitus, galactorrhea, amenorrhea, gynecomastia, erectile dysfunction, neutropenia, seizure threshold lowering, personality changes and suicidality ( 10 , 12 ). In case of overdose, patients may suffer from tachycardia, agitation, hyperpyrexia, leukocytosis, elevated creatine phosphokinase levels, paradoxical miosis mimicking opioid or α2-agonist intoxication ( 13 ), dysarthria, low level of consciousness, dry mouth, ataxia and coma.…”
Section: Introductionmentioning
confidence: 99%